Thermal comfort investigation on a naturally ventilated twostorey residential house in Malaysia - Malek N.A.; Khairuddin M.H.; Rosli M.F. (Institute of Physics Publishing, 2023)
Air; Ceilings; Computational fluid dynamics; Flow patterns; Houses; Housing; Temperature distribution; Thermal comfort; Ventilation; Airflow patterns; ASHRAE standards; Building designers; Commercial codes; Human thermal comfort; Mechanical ventilation; Residential house; Thermal comfort level; Heating